Potent LpxC Inhibitors with In Vitro Activity against Multidrug-Resistant Pseudomonas aeruginosa - Krause, Kevin M. (Antimicrob Agents Chemother, 2019)
New drugs with novel mechanisms of resistance are desperately needed to address both community and nosocomial infections due to Gram-negative bacteria. One such potential target is LpxC, an essential enzyme that catalyzes the first committed step of lipid A biosynthesis. Achaogen conducted an extensive research campaign to discover novel LpxC inhibitors with activity against Pseudomonas aeruginosa. We report here the in vitro antibacterial activity and pharmacodynamics of ACHN-975, the only molecule from these efforts and the first ever LpxC inhibitor to be evaluated in phase 1 clinical trials. In addition, we describe the profiles of three additional LpxC inhibitors that were identified as potential lead molecules. These efforts did not produce an additional development candidate with a sufficiently large therapeutic window and the program was subsequently terminated.